Improving the Membrane Permeability of 5‑Fluorouracil via Cocrystallization - Dai, Xia-Lin; Li, Song; Chen, Jia-Mei; Lu, Tong-Bu (Crystal growth & design, 2016)
Pharmaceutical cocrystallization is proposed as a new method to enhance membrane permeability of a BCS class III model drug, 5-fluorouracil (5FU). Three cocrystals of 5FU, 5FU/3-hydroxybenzoic acid (1), 5FU/4-aminobenzoic acid (2), and 5FU/cinnamic acid (3), were successfully synthesized by a slurry method or a liquid-assisted grinding process. Spectroscopic methods, thermal analysis, and X-ray diffraction were used to characterize these new forms. The permeability was studied using a Franz diffusion cell and silicone membrane. All of the cocrystals showed improved membrane permeability compared to free 5FU. The cumulative amount per unit area of permeated 5FU in the first 10 h for 1–3 was increased by 41, 70, and 83%, and the steady penetration rates of 1–3 were increased by 38, 66, and 79%, respectively, as compared to the pure drug. Structure–permeability correlation study finds a link between intermolecular interactions and molecular packing in cocrystals and their permeability behavior and has important implications for use of a cocrystallization approach to improve drugs’ permeability in the pharmaceutical field.